2002
DOI: 10.1021/es011226k
|View full text |Cite
|
Sign up to set email alerts
|

Raman Study of Aluminum Speciation in Simulated Alkaline Nuclear Waste

Abstract: The chemistry of concentrated sodium aluminate solutions stored in many of the large, underground storage tanks containing high-level waste (HLW) at the Hanford and Savannah River Nuclear Reservations is an area of recent research interest. Not only is the presence of aluminate in solution important for continued safe storage of these wastes, the nature of both solid and solution aluminum oxyhydroxides is important for waste pretreatment. Moreover, for many tanks that have leaked high aluminum waste in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 26 publications
1
55
1
Order By: Relevance
“…Controversy still exists even as to the number of complexes formed and in particular whether the highest-order mononuclear species is Pb(OH) 3 -or Pb(OH)/ - [13,17]. Clarification of this issue is important for modeUng the behavior of Pb(II) in high pH solutions found in nuclear wastes [ 18] and industrial Bayer process "l iquors" [ 19]. As for the Pb 2 +Jsoi-system discussed above, a major reason for this situation is that most of the usual speciation techniques are thwarted by the precipitation of sparingly soluble Pb(ll) salts.…”
Section: Case Study 2: Pbo (Unfinished Business)mentioning
confidence: 99%
“…Controversy still exists even as to the number of complexes formed and in particular whether the highest-order mononuclear species is Pb(OH) 3 -or Pb(OH)/ - [13,17]. Clarification of this issue is important for modeUng the behavior of Pb(II) in high pH solutions found in nuclear wastes [ 18] and industrial Bayer process "l iquors" [ 19]. As for the Pb 2 +Jsoi-system discussed above, a major reason for this situation is that most of the usual speciation techniques are thwarted by the precipitation of sparingly soluble Pb(ll) salts.…”
Section: Case Study 2: Pbo (Unfinished Business)mentioning
confidence: 99%
“…Recently, we have shown that the Raman spectra of concentrated Al 2 O 3 -Na 2 O-H 2 O solutions are strongly dependent on the chemical composition of the solution. 10 A detailed description of the Raman data and the accompanying chemical and physical property measurements (temperature, density, relative humidity and molar concentrations) over a broad range of sample compositions has been reported. 10 In this work, we applied Raman spectroscopy and multivariate curve resolution to the Raman data.…”
Section: Introductionmentioning
confidence: 99%
“…Al solubility may be controlled by sodium-aluminate phases (Johnston et al, 2002), phyllosilicates, or zeolites. Mg solubility appears to be controlled by brucite during both the conditioning and transient intervals, but analysis of steady-state releases at high pH suggests the formation of a Mg-silicate or Mg-aluminosilicate.…”
mentioning
confidence: 99%